Physics and Chemistry of Solid State Direct Reduction of Iron Ore by Hydrogen Plasma - Sabat, Kali Charan (Physics and Chemistry of Solid State, 2021)
Presently, Iron is produced from iron ores by using carbon from coal. The production process is consisting of many stages. The involvement of multi-stages needs high capital investments, large-scale equipments, and produces large amounts of carbon dioxide (CO2) responsible for environmental pollution. There have been significant efforts to replace carbon with hydrogen (H2). Although H2 is the strongest reductant, it still also has thermodynamic and kinetic limitations. However, these thermodynamic and kinetic limitations could be removed by hydrogen plasma (HP). HP comprises rovibrationally excited molecular, atomic, and ionic states of hydrogen. All of them contribute to thermodynamic advantage by making the Gibbs standard free energy more negative, which makes the reduction of iron oxides feasible at low temperatures. Apart from the thermodynamic advantage, these excited species increase the internal energy of HP, which reduces the activation energy, thereby making the reduction easier and faster. Apart from the thermodynamic and kinetic advantage of HP, the byproduct of the reaction is environmentally benign water. This review discusses the physics and chemistry of iron ore reduction using HP, emphasizing the solid-state reduction of iron ore. HP reduction of iron ore is a high potential and attractive reduction process.